THE FILIPINO LEARNER: PHYSICAL ATTRIBUTES - Favila, Salve A. (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
Existing researches about the attributes of the Filipino learnersÂ Â  are found to be fragmented and limited to a particular grade level and learning areas. This condition indicates the dearth of studies as regards the developmental characteristics of the Filipino learners.Â  The learnersâ attributes and developmental characteristics are important data in drawing program standards and learning area competencies in educational practice. This research explores the physical attributes of Filipino learners with the end view that such characteristics will provide data for developmental tasks of Filipino children. Various theories and expertâs assumptions guided this research. Gallahue propelled the physical attributes of the learners. Using the case study method with research techniques such as interview of students, teachers and parents, observation and survey of teachers, result reveal that Filipino learners can be at par with the characteristics and developmental tasks presented by educational theorist except in physical education where learners are lower by one year in the developmental attributes presented by Gallahue. A number of tasks of Filipino learners are shown within the context of Filipino culture and realities. For instance, developmental characteristics of Filipino learners are different from the western attributes because they were observed using our own Philippine context. Since this research is exploratory, new areas of study have emerged. The physical attributes may be explored not only in Physical Education classes but also in learning areas such as arts, playing of musical instruments or industrial arts. The cognitive dimension may be studied through the language used by the children. Similarly, moral, social and emotional components may be studied through language, stories and everyday life situations of children. Studies comparing the developmental characteristics of children and the competencies of various learning areas in the K-12 curriculum may also be investigated.